The efficacy and safety of immunotherapy as first−line treatment for extensive-stage small cell lung cancer: evaluating based on reconstructed individual patient data - Zhang, Shuang; Li, Shuang; Cheng, Ying (Frontiers in Oncology, 2024)
Objective: Selecting between programmed cell death ligand1 (PD-L1) inhibitor or programmed cell death 1 (PD-1) inhibitor plus chemotherapy as first-line treatment for extensive-stage small cell lung cancer (ES-SCLC) patients urgently needs to be answered. Methods: Eligible phase 3 randomized clinical trials evaluating regimens based on PD-1/PD-L1 inhibitors as first-line treatment in ES-SCLC patients were systematically searched on the PubMed, Cochrane Library databases, and major international conferences from January 01, 2018 to September 18, 2023. The individual patient data (IPD) were recuperated from the Kaplan–Meier curves of the overall survival (OS) and progression-free survival (PFS) of the included studies using the IPDfromKM method. The reconstructed data were pooled into unified arms, including the PD-L1 inhibitor plus chemotherapy group (PD-L1 group), PD-1 inhibitor plus chemotherapy group (PD-1 group), and PD-1 (L1) inhibitor and chemotherapy plus other (anlotinib group, tiragolumab group, and tremelimumab group). Subsequently, the PD-L1 group was indirectly compared to the other groups. A standard statistical analysis was conducted using the "survival" package for the time-to-event endpoint. The primary outcomes were the OS and PFS of the PD-L1 group and the PD-1 inhibitor group. The secondary outcomes included safety and the 12, 24-month restricted mean survival time (RMST) of the PD-L1 group and PD-1 group. Results: A total of 9 studies including 11 immunotherapy cohorts were included. No significant difference in PFS (hazard ratio [HR]: 0.96, 95% confidence interval [CI]:0.86-1.06), OS (HR: 0.94, 95%CI:0.84-1.05) and 12-month, 24-month RMST for OS (P=0.198 and P=0.216, respectively) was observed between the PD-L1 group and the PD-1 group. In contrast, the anlotinib group showed significantly better OS (HR:0.70, 95%CI:0.55-0.89), PFS (HR:0.69, 95%CI:0.58-0.83), and RMST for OS compared to the PD-L1 group. The incidence of ≥grade 3 treatment-emergent adverse events (TEAEs) was significantly higher in the PD-1 group compared to the PD-L1 group (85.4% vs 69.6%, P<.001), while the incidence of irAEs was similar between the two groups. Conclusion: This reconstructed IPD analysis revealed that PD-1 inhibitors plus chemotherapy achieved similar efficacy to PD-L1 inhibitors plus chemotherapy as first-line treatment in ES-SCLC patients, while PD-L1 inhibitors plus chemotherapy had a better safety profile.